Pengaruh Ukuran Perusahaan Dan Profitabilitas Terhadap Struktur Modal Perusahaan Manufaktur Subsektor Makanan Dan Minuman Yang Terdaftar Di Bursa Efek Indonesia - saputra, ferry dhita; Suarmanayasa, I Nengah (Jurnal Akuntansi Profesi, 2021)
This research intended to examine the effect of company size and profitability on the capital structure in companies manufacture sub-sector food and beverage at Indonesian stocks exchange. The research design used was causal quantitative research. The subject on this research are companies manufacture sub-sector food and beverage at Indonesian stocks exchange,and object on this research are company size and profitability.Â  Data collected by document recording and data analysis technique used was multiple linear regression analysis. The results of this study are: (1) company size and profitability has significant effect on the capital structure. (2) company size has a significant and positive effect on the capital. (3) profitability has a significant and positive effect on the capital structure in companies manufacture sub-sector food and beverage at Indonesian stocks exchange.Keywords: Company Size, Profitability,Capital Structure